Caring for Persons Living With Dementia During the COVID-19 Pandemic: Advocacy Perspectives From India - D'Cruz, Migita; Banerjee, Debanjan (Frontiers in Psychiatry, 2020)
The Coronavirus disease 2019 (COVID-19) pandemic has presented an unprecedented threat to global public and psychosocial health. Certain vulnerable populations, especially the older adults, are at disproportionate risks both to the physiological and social effects of the outbreak. A special section among them who face unique challenges during this pandemic, are those living with neurocognitive disorders, like dementia. Limited research in the field shows ApoE4 allele to confer an increased risk for COVID-19 severity, while the behavioural problems associated with dementia reduces compliance to precautionary measures, thereby exposing them to the virus and increasing caregiver strain. Reduced healthcare access, limited resources and fear of the infection act as major barriers to dementia care during such a crisis. Besides, there are the additional burden of stigma, abuse, ageism and financial impoverishment. Institutionalization, loneliness and lack of stimulation can potentially accelerate the cognitive decline and worsen the behavioral and psychological problems. India has been one of the worst hit countries by COVID-19 and shares a significant dementia load. As the country is aging fast along with the world, this commentary reviews the risks of people living with dementia during the pandemic and discusses certain advocacies for their care.